Exploring nurses’ experiences of the OSCE exam: a qualitative study - Parastoo Majidipour; Saeed Jameh Shourani; Parvaneh Asadi; Akram Rahmani; Hossein Parsa (BMC Nursing, 2026)
Abstract Background The Objective Structured Clinical Examination (OSCE) is a performance-based assessment method widely utilized in health professions education to evaluate clinical competence. However, understanding how practicing nurses experience this structured evaluation in clinical settings is essential for improving its implementation and educational value. This study aimed to explore nurses’ lived experiences of the OSCE exam. Methods A qualitative content analysis design was conducted at Imam Reza Hospital in Kermanshah, Iran. Fourteen registered nurses were selected using purposeful sampling with maximum variation to capture diverse clinical perspectives. Data were collected through semi-structured face-to-face interviews. The interviews were transcribed verbatim and analyzed inductively using conventional qualitative content analysis. MAXQDA software was used for data organization and management. Results Analysis of the data revealed eight main themes: (1) meaning of the OSCE, (2) personal experience with the OSCE, (3) impact of the OSCE on professional performance, (4) challenges of OSCE implementation, (5) the OSCE in the teaching-learning process, (6) advantages and disadvantages of the OSCE, (7) expectations from the OSCE, and (8) suggestions for improvement. While participants recognized the OSCE as a highly comprehensive and educational tool that links theory to clinical practice, they also highlighted significant operational challenges, including physical fatigue, long waiting times, and stress related to station scheduling. Conclusions Nurses perceive the OSCE as a valuable educational approach for reviewing clinical knowledge and verifying competencies. However, its effectiveness is heavily influenced by scheduling, organization, and station design. Aligning stations with ward-specific clinical demands and managing participant fatigue are critical to maximizing the educational and assessment utility of the OSCE. Clinical trial registration number Not applicable.